MANIPULATION AND ABUSE OF POWER IN ‘ANIMAL FARM’ - Bhagwinder Kaur (International Educational Journal of Science and Engineering, 2024)
Animal Farm by George Orwell is widely recognized as a powerful political allegory that exposes the dangers of power, propaganda, and the corruption of revolutionary ideals. The novel narrates the story of farm animals who revolt against their human master in the hope of establishing a society based on equality, justice, and collective welfare. Inspired by the revolutionary ideas of Old Major, the animals overthrow human rule and establish the principles of Animalism. Initially, the rebellion appears successful as the animals work together to build a fair and cooperative community. However, as the pigs gradually assume leadership, the ideals of the revolution begin to deteriorate. Leaders such as Napoleon consolidate power through propaganda, manipulation of laws, and the use of fear and violence. The character of Squealer plays a crucial role in shaping the animals’ perception of reality through persuasive language and misinformation. Meanwhile, hardworking animals like Boxer symbolize the exploited working class whose loyalty is ultimately betrayed. The novel also reflects historical events such as the Russian Revolution and the rise of authoritarian rule under Joseph Stalin. Through satire and allegory, Orwell demonstrates how revolutions that promise equality can be corrupted by ambitious leaders. The novel ultimately serves as a timeless warning about political manipulation, abuse of power, and the vulnerability of societies to authoritarian control.